Efektivitas Pengelolaan Perpustakaan Daerah di Kabupaten Bone Bolango Provinsi Gorontalo - Fatmawaty Anggowa; Abdul Kadim Masaong; Nur Eng Mokodompit (Universitas Muhammadiyah Gorontalo, 2017)
Abstract This study aims to determine how the effectiveness of the management of library office area at Bone Bolango regency. The method used in the implementation of the research is descriptive quantitative methods, data collection technic used are observation, questionaire and documentation. The data analysis technic using injection analysis and described descriptively. With a sample size of 30 people were taken from the entire population of 30 people. The result showed that; 1. The effective implementation of the management plant of library office area at the Bone Bolango regency category quite effective. 2. The effectiveness of the implementation of the organization management plant of library at Bone Bolango regency category quite effective. 3. The effectiveness of the implementation of the management plan of library at Bone Bolango regency success and target priority program categories is quite effective. 4. Monitoring and evaluation the management of library office area at Bone Bolango regency category effective because according to the results of the study support system has been imposed only madequate facilities. Abstrak Penelitian ini bertujuan untuk mengetahui seberapa efektivitas pengelolaan Perpustakaan Daerah Kabupaten Bone Bolango.Metode yang digunakan pada pelaksanaan penelitian adalah metode kuantitatif deskriptif, teknik pengumpulan data yang digunakan adalah observasi, angket dan dokumentasi. Sedangkan teknik analisis data mengunakan analisis injek dan diurakan secara deskriptif. Dengan jumlah sampel 30 orang yang di ambil dari seluruh populasi yang berjumlah 30 orang. Hasil penelitian menunjukkan bahwa; 1)tingkat efektivitas pelaksanaan perencanaan pengelolaan Perpustakaan Daerah Kabupaten Bone Bolango kategori cukup efektif, 2)Tingkat efektivitas pelaksanaan pengorganisasian pengelolaaan Perpustakaan Daerah Kabupaten Bone Bolango kategori cukup efektif; 3)Tingkat efektivitas pelaksanaan pengelolaan Perpustakaan Daerah Kabupaten Bone Bolango mengutamakan keberhasilan dan sasaran program kategori cukup efektif. 4)Monitoring dan evaluasi Pengelolaan Perpustakaan Daerah Kabupaten Bone Bolango ketegori efektif karena menurut hasil penelitian system yang diberlakukan sudah menunjang hanya saja fasilitas yang kurang.